HUBUNGAN ANTARA PENERIMAAN DIRI DENGAN RESIENSI PADA REMAJA DI PANTI ASUHAN - ANANDA PRIMA KRISTIANTI; Wahyuni Kristinawati (Wacana Psikokultural, 2024)
Poverty, divorce, and other problems in families in Indonesia is what makes it difficult for family to provide the needs of their children. So there are adolescents who live in orphanages. New situations, as well as changes in habits, are the results from the separation of children from their families. The lack of attention quality caused by the large difference in number between the caregiver and the teenager results in adolescents experiencing greater psychological pressure compared to adolescents who do not live in orphanages. To keep struggling under this pressure, adolescents need to have resilience in dealing with all those pressure. In addition, adolescents also need to have self-acceptance in living their daily lifes, because self-acceptance is also able to help adolescents to accept their strengths and weaknesses, and other person. Therefore, this study aims to determine the correlations between self-acceptance and resilience in adolescents living in Woro Wiloso orphanage, Salatiga. The methods used in this research was quantitative with a pearson correlation design. This research used non-probability sampling technique by involving 47 participants. The data were collected by using self-acceptance and resilience(questionnaire) scale. The result of this research showed that there was a correlation between self-acceptance and resilience in adolescents who live in orphanage (r-test = 0,282 with sig. = 0,055). The results of this study also reveals that the ability to overcome difficult situation is influenced by self-acceptance Keywords: Self-acceptance, Resilience, Adolescents, Orphanage